2018
DOI: 10.1088/1361-6560/aabfa0
|View full text |Cite
|
Sign up to set email alerts
|

Automated human skull landmarking with 2D Gabor wavelets

Abstract: Landmarking of CT scans is an important step in the alignment of skulls that is key in surgery planning, pre-/post-surgery comparisons, and morphometric studies. We present a novel method for automatically locating anatomical landmarks on the surface of cone beam CT-based image models of human skulls using 2D Gabor wavelets and ensemble learning. The algorithm is validated via human inter- and intra-rater comparisons on a set of 39 scans and a skull superimposition experiment with an established surgery planni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…The cephalometric analysis aims to set landmarks of CT(CBCT) scans which serve as an important factor in the alignment of a skull. These measurements can also be used as surgery planning parameters or pre-and post-surgery comparisons [149,150].…”
Section: Automatization Of Cephalometric Analysismentioning
confidence: 99%
“…The cephalometric analysis aims to set landmarks of CT(CBCT) scans which serve as an important factor in the alignment of a skull. These measurements can also be used as surgery planning parameters or pre-and post-surgery comparisons [149,150].…”
Section: Automatization Of Cephalometric Analysismentioning
confidence: 99%
“…A promising development is the automatic 3D landmarking using artificial intelligence. Some recent studies have reported errors below 2 mm [22,23], making automatic 3D landmarking a potential alternative. However, as the landmarks are not used for matching but only function as rotation points, the identification of the landmarks has become of little concern.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Using both sources of information can improve landmarking accuracy (de Jong et al, 2016). It is also possible to combine several landmarking algorithms into a combined method (ensemble) (de Jong et al, 2018b) which can increase flexibility (de Jong et al, 2018a).…”
Section: Landmarkingmentioning
confidence: 99%
“…Replication efforts in genetic studies of facial traits therefore require reproducibility of quantification. Reliability of manual landmarking efforts have been evaluated in some studies (Fagertun et al, 2014; Katina et al, 2015; de Jong et al, 2018a). The agreement between raters was consistently reported to be between 1 and 2 mm across landmarks.…”
Section: Reliability and Heritabilitymentioning
confidence: 99%
See 1 more Smart Citation